Global Strategies of Thai Small- and Medium-Sized Enterprises (SMEs): A Study of How SMEs Can Successfully Expand into Global Markets - Tongdhamachart, Niracharapa (Digital Repository of Theses, 2025)
The study examines the global strategies of Thai Small and Medium-Sized Enterprises (SMEs), with a particular focus on the challenges, success factors, and practical solutions associated with international market expansion. SMEs are vital to Thailand’s economy, accounting for 99.5% of all businesses and contributing approximately 35% of GDP. However, they face substantial barriers in globalizing, including financial limitations, bureaucratic hurdles in accessing government support, cultural unfamiliarity, and limited international experience. Adopting a mixed-methods approach, the study integrates quantitative data from 400 SMEs with qualitative insights derived from six in-depth interviews. It investigates the influence of four key constructs—technology adaptation, government support, cultural adaptability, and international experience—on international business success. The findings reveal that technology adaptation is the most influential driver. SMEs with strong digital marketing and e-commerce capabilities showed significant positive correlations with revenue growth (β = 0.38, p < 0.001) and international market expansion (r = 0.60). Government support was also statistically significant (β = 0.22, p < 0.001), though only 25% of SMEs actively utilized it, with 60% citing administrative complexity as a major barrier. Cultural adaptability, while statistically insignificant (β = 0.10, p > 0.05), was highlighted as a practical necessity for managing cross-cultural communication and localization. International experience emerged as the strongest overall predictor of global success, with regionally diversified SMEs achieving up to 70% higher market penetration and 65% greater revenue stability (β = 0.43, p < 0.001). The research offers a comprehensive strategic framework for enhancing the global competitiveness of Thai SMEs. Key recommendations include streamlining government funding access, expanding digital capability training, and promoting international partnerships. While the findings have broader implications for emerging economies, limitations related to geographic and sectoral specificity suggest future research should adopt longitudinal designs or focus on industry-specific dynamics.